Segmented swept source optical coherence tomography angiography assessment of the perifoveal vasculature in patients with X-linked juvenile retinoschisis: a serial case report - Stringa, Francesco (Int Med Case Rep J, 2017)
PURPOSE: To describe perifoveal microvascular changes occurring in X-linked juvenile retinoschisis (XLRS) using swept source optical coherence tomography angiography (SS OCTA). PATIENTS AND METHODS: This is a serial case report of three patients. Retrospective data of patients affected by XLRS were collected. Structural optical coherence tomography (OCT) and color fundus photography (CFPh) were carried out with Topcon(®) OCT 2000 3D OCT as part of the standard care. Two patients were imaged on Topcon Atlantis(®) SS OCTA and one on Topcon Triton(®) SS OCTA. SS OCTA images were acquired using the 3 × 3 mm fovea-centered cubes scanning protocol. Analysis of both perifoveal superficial vascular plexus (pSVP) and perifoveal deep vascular plexus (pDVP) was performed by two observers after automated segmentation. RESULTS: Four eyes of three males (mean age 14 ± 3.8 years) were analyzed. All eyes showed foveoschisis on CFPh images. OCT B-scans of three eyes showed schistic cysts in the ganglion cell layer, inner nuclear layer (INL) and outer nuclear layer (ONL); in one eye, cysts were depicted in INL and ONL only. In two eyes, SS OCTA showed abnormal foveal avascular zone (FAZ) shape in the pSVP, and in the other two, FAZ shape was abnormal in both plexuses. In all eyes, retinal vascular abnormalities (ie, microvascular protrusions) were present in pDVP. CONCLUSION: SS OCTA can depict perifoveal microvascular changes in young patients affected by XLRS. In this study, the structural and vascular changes seem to be more evident in the pDVP and may represent a useful biomarker of prognosis.